Контроль дисперсии параметров деформации пластмасс для изоляции и оболочек кабелей в пожаробезопасном исполнении - Золотарев, Владимир Михайлович; Васильева, О. В.; Щебенюк, Леся Артемовна (НТУ "ХПИ", 2012)
Выполнен анализ механических свойств наполненного и ненаполненного ПВХ-пластификата для пожаробезопасных кабелей.

The analysis of mechanicals properties of full and not full polyvinylchloride plasticate.
Dispersion control of deformation parameters in plastic materials used for isolation and covers of fireproof cables
Keywords: свойства механические; полимеры; пластификат; поливинилхлорид; fireproof cables; plastic materials; dispersion control